Flexible thermoelectric cooler with optimized fill factor and radiative cooling integration for energy-efficient wearable thermal management - Jakrit Gobpant; Aparporn Sakulkalavek; Pannarai Sriniratkul; S. Siva Sankara Sai; Chalermpol Rudradawong; Jianghan Tian; V.X. Nguyen; Takahito Ono; Nguyen Van Toan (Sustainable materials and technologies, 2025)
The growing demand for skin-interfaced electronics in health monitoring, sports, and personal comfort highlights the need for compact, energy-efficient, and conformable cooling systems. However, existing thermoelectric coolers (TECs) are rigid, bulky, and power-intensive, making them unsuitable for wearable applications. To address this limitation, we present a flexible thermoelectric cooler (FTEC) with a compact footprint of 40 × 40 × 2.26 mm 3 , featuring discrete p- and n-types thermoelectric leg arrays with systematically varied fill factors (FF = 9 %, 16 %, 25 %, and 36 %). Optimization revealed that the 16 % FF configuration provides the most energy-efficient architecture, achieving a cold-side temperature of −5.9 °C and a coefficient of performance (COP) of 3.25 at 6 W input, while balancing cooling capacity and electrical loss. To improve heat dissipation without increasing bulk, ultrathin graphite and radiative cooling (RC) layers were integrated. Three configurations, including baseline (no thermal layer), graphite-enhanced, and RC-enhanced FTECs, were systematically evaluated. Under ambient conditions (33 °C), the RC- enhanced FTEC maintained a cold-side temperature of approximately 23 °C for 6 h during low-current operation of 0.3 A. Beyond intrinsic performance, the optimized FTEC was benchmarked against both commercial rigid TEC modules and state-of-the-art flexible TECs. Compared to widely used Peltier devices (TEC1–12705 and TEC1–12710), our FTEC achieved comparable ΔT with nearly 65 % lower power consumption, owing to fill factor optimization and RC-enhanced heat rejection. Mechanical flexibility was validated through bending tests, confirming both thermal and electrical stability. Finally, integration with an ESP32-based proportional–integral–derivative (PID) control system enabled real-time wearable cooling, successfully reducing skin temperature from 33 °C to 31 °C in on-body trials. This work demonstrates.
Keywords: Advanced Thermoelectric Materials and Devices; Thermal Radiation and Cooling Technologies; Innovative Energy Harvesting Technologies